EXTRA-CLASS EDUCATION AS A BASIS FOR FORMING STUDENTS' COGNITIVE INTEREST IN TEACHING BIOLOGY - Salybekova N.N.; Kenshimbayeva N.K. (Scientific Research and Experimental Development, 2023)
The type of cognitive activity of students outside of classes, its formation and development is associated with cognitive interest, learning motives and other factors. The works of a number of psychologists and didacticists are devoted to cognitive interest and its formation. Some of them reveal the psychological nature of curiosity [1], others consider cognitive interest as a motive of behavior (Leontiev A. N., Bozhovich L. I.), the preferred orientation of a person, his attention (Ribot G., Dobrynin N. F.), his thoughts, the orientation of his thoughts (S. L . Rubinshtein), representation of mental and emotional activity (Strong E.K., Rubinshtein S.L.), life meaning and emotional attractiveness of a person (Kovalev A.G.), as an important tools of learning (Babansky Yu.K., Traitak D. I.) and others. Shchukina G.I. paid a lot of attention to study the cognitive interest and cognitive activity of students. She describes cognitive interest as "a complex attitude to objects and phenomena of the surrounding reality, expressing a person's desire to comprehensively study, to know their important properties." According to Shchukina G.I., the cognitive interest of students is focused on obtaining knowledge, as well as on the learning process itself, and to the cognitive activity. Treitak D. considers cognitive interest as "an unconstrained emotional orientation of the student's psyche to the constant aspiration for active knowledge of the subject of study."[2]. Using the methodology of content analysis, Lanina I.Ya. gives the following definition of cognitive interest: “a student’s cognitive interest is a person’s positive attitude to the knowledge of the surrounding reality, which is aimed at actively mastering subjectively significant learning objects” [3].